2019
DOI: 10.1016/j.cpr.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of therapist effects: A critical narrative update and refinement to review

Abstract: Objective: To review the therapist effects literature since Baldwin and Imel's (2013) review. Method: Systematic literature review of three databases (PsycINFO, PubMed and Web of Science) replicating Baldwin and Imel (2013) search terms. Weighted averages of therapist effects (TEs) were calculated, and a critical narrative review of included studies conducted. Results: Twenty studies met inclusion criteria (3 RCTs; 17 practice-based) with 19 studies using multilevel modeling. TEs were found in 19 studies. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
170
1
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(209 citation statements)
references
References 43 publications
12
170
1
10
Order By: Relevance
“…Notably, the non-NHS sector therapist effects were qualitatively lower than is typically reported in practice-based studies (Baldwin & Imel, 2013;Johns et al, 2019). This is consistent with Johns et al's (2019) (e.g., organizational factors), thereby reducing the relative contribution of the therapist to outcome. Clinical populations in some care contexts may be much more highly selected than in other contexts.…”
Section: Discussionsupporting
confidence: 66%
“…Notably, the non-NHS sector therapist effects were qualitatively lower than is typically reported in practice-based studies (Baldwin & Imel, 2013;Johns et al, 2019). This is consistent with Johns et al's (2019) (e.g., organizational factors), thereby reducing the relative contribution of the therapist to outcome. Clinical populations in some care contexts may be much more highly selected than in other contexts.…”
Section: Discussionsupporting
confidence: 66%
“…The authors demonstrated an association between certain utterances and clinical outcome. Given that there is extensive literature that supports the idea that there is significant variance in therapist competence (Johns et al, 2019), it is not surprising that the findings from this study also suggest this. Even studies that have not been conducted in real-world settings report this variance.…”
Section: Discussion and Implications For Practicesupporting
confidence: 56%
“…These so-called therapist effects have been found consistently across different patient groups and clinical settings and have been estimated to account for approximately 5% of the variance in patient outcomes (see Johns, Barkham, Kellett, & Saxon, 2019, for a recent review). These so-called therapist effects have been found consistently across different patient groups and clinical settings and have been estimated to account for approximately 5% of the variance in patient outcomes (see Johns, Barkham, Kellett, & Saxon, 2019, for a recent review).…”
Section: Introductionmentioning
confidence: 99%
“…One of the clearest findings of psychotherapy research in recent years is that therapists differ in their average effectiveness. These so-called therapist effects have been found consistently across different patient groups and clinical settings and have been estimated to account for approximately 5% of the variance in patient outcomes (see Johns, Barkham, Kellett, & Saxon, 2019, for a recent review). In contrast to this consistent support for the relevance of therapist effects, it is less clear which therapist characteristics are responsible for these effects (Heinonen & Nissen-Lie, 2019).…”
Section: Introductionmentioning
confidence: 99%